PENULISAN ULANG CERITA RAKYAT BUTON ‘BATU POARO’: STRATEGI MENULIS CERITA ANAK - Rina Ratih Sri Sudaryani; Iis Suwartini; Nasrilia Rahmadina (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2025)
Indonesian folktales that are full of local wisdom and life values will experience extinction if rewriting is not done. The purpose of this study is to describe the rewriting of Buton folklore “Batu Poaro” as a creative writing strategy. This research is qualitative in nature using the documentation method. Data were collected from various references. The data source of this research is a folktale entitled “Batu Poaro” from Buton Island, Southeast Sulawesi (Center for Language Development and Development, Department of Education and Culture, 1998). The technique of writing folklore used is as stated by Rampan, namely (1) how to open the story, (2) lead to excitement, (3) mid-story, (4) climax, and (5) convey the meaning of the story. The result of this research is a folktale 'Batu Poaro' from Buton which was originally in the local language has been rewritten into Indonesian and became an interesting children's reading. The folktale 'Batu Poaro' has been published together with other Buton and Wakatobi folktales by Pustaka Pelajar publisher in 2023 entitled Wa Ode from Wangi-Wangi. Keywords; Batu Poaro, Buton, Folklore, Rewriting.